Influência da formação de pozolanas com adição de metacaulim em concreto de alta resistência - Soares, Faisy Paulino Pereira (2013)
The need to build durable structures and resistant to harsh environments enabled the development of high strength concrete, these activities generate a high cement consumption, which implies factor in CO2 emissions. Often the desired strength is not achieved using only the cement composition. This study aims to evaluate the influence of pozzolans with the addition of metakaolin on the physical mechanics of high strength concrete comparing them with the standard formulation. Assays were performed to characterize the aggregates according to NBR 7211, evaluation of cement and coarse aggregate through the trials of petrography (NBR 15577-3/08) and alkali-aggregate reaction (NBR 15577-05/08). Specimens were fabricated according to NBR 5738-1/04 with additions of 0%, 4%, 6%, 8% and 10% of metakaolin for cement mortars CP V in the formulations. For evaluation of the concrete hardened in fresh state and scattering assays were performed and compressive strength in accordance with the NBR 7223/1992 and NBR 5739-8/94 respectively. The results of the characterization of aggregates showed good characteristics regarding size analysis and petrography, as well as potentially innocuous as the alkali-aggregate reaction. As to the test of resistance to compression, all the formulations with the addition of metakaolin showed higher value at 28 days of disruption compared with the standard formulation. These results present an alternative to reduce CO2 emissions, and improvements in the quality and durability of concrete, because the fine particle size of metakaolin provides an optimal compression of the mass directly influencing the strength and rheology of the dough